Penerapan Sistem Budidaya Minapadi Organik sebagai Upaya Peningkatan Produktivitas Pertanian di Desa Wonopringgo, Kabupaten Pekalongan: Implementation of Organic Paddy-Fish Cultivation System as an Effort to Improve Agricultural Productivity in Wonopringgo Village, Pekalongan Regency - Ariadi, Heri; Al Ramadhani, Farchan Mushaf; Mardiana, Tri Yusufi; Nisa, Silvianita Khoirun; Maharani, Kayla; Sapto, Dimas Hari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The decline in rice productivity is attributed to the excessive use of chemical fertilizers, which leads to soil saturation and adverse environmental impacts. The purpose of this community service is to implement an organic minapadi cultivation system as a strategy to increase agricultural productivity in Wonopringgo Village, Pekalongan Regency. The community service activity was carried out from June to August 2025, involving 24 partner farmers through observation, extension, and practical methods of creating organic minapadi cultivation demonstration plots. The results of the activity showed a significant increase in farmers' knowledge, experience, and awareness of the organic minapadi system. The number of farmers who understood the concept of minapadi increased from 5 to 22, while the understanding of organic farming rose from 2 to 20. In addition, all farmers gained direct experience through extension activities and field practice. An increase in knowledge of the benefits of minapadi was also seen, from previously only three farmers to 24 farmers who were aware of it. This confirms that the integrated extension approach is efficient in transferring knowledge to partners. Overall, the implementation of organic minapadi (rice-fish farming) in Wonopringgo Village not only provides ecological benefits in the form of improved soil fertility and pest control, but also increases economic opportunities through crop diversification. This activity has the potential to become a pilot model that can be replicated in other areas with similar agro-ecosystem conditions, while also supporting sustainable agricultural development.